Comparison of Translation Techniques Between Human and Microsoft Translator (Windows 11) in Translating Folklores - Br Karosekali, Stephani Caludia; Sipayung, Kammer Tuahman; Saragi, Christina Natalina (LPPM Universitas HKBP Nommensen, 2024)
The purpose of this study is to describe the comparison of folklore translation techniques performed by human and Microsoft translator (windows 11). This research was conducted using Descriptive Qualitative method. The research subjects were taken from folklores titled